Activation of autophagy in human skeletal muscle is dependent on exercise intensity and AMPK activation. Issue 8 (8th May 2015) - Schwalm, Céline; Jamart, Cécile; Benoit, Nicolas; Naslain, Damien; Prémont, Christophe; Prévet, Jérémy; Van Thienen, Ruud; Deldicque, Louise; Francaux, Marc
Abstract : In humans, nutrient deprivation and extreme endurance exercise both activate autophagy. We hypothesized that cumulating fasting and cycling exercise would potentiate activation of autophagy in skeletal muscle. Well‐trained athletes were divided into control ( n = 8), low‐intensity (LI, n = 8), and high‐intensity (HI, n = 7) exercise groups and submitted to fed and fasting sessions. Muscle biopsy samples were obtained from the vastus lateralis before, at the end, and 1 h after a 2 h LI or HI bout of exercise. Phosphorylation of ULK1 Ser317 was higher after exercise (P< 0.001). In both the fed and the fasted states, LC3bII protein level and LC3bII/I were decreased after LI and HI (P < 0.05), while p62/ SQSTM1 was decreased only 1 h after HI (P < 0.05), indicating an increased autophagic flux after HI. The autophagic transcriptional program was also activated, as evidenced by the increased level of LC3b, p62/ SQSTM1, GabarapL1, and Cathepsin L mRNAs observed after HI but not after LI. The increased autophagic flux after HI exercise could be due to increased AMP‐activated protein kinase α (AMPKα) activity, as both AMPKα Thr72 and ACC Ser79 had a higher phosphorylation state after HI (P < 0.001). In summary, the most effective strategy to activate autophagy in human skeletal muscle seems to rely on exercise intensity more than diet.— Schwalm, C., Jamart, C., Benoit, N., Naslain, D., Prémont, C., Prévet, J., Van Thienen, R., Deldicque, L., Francaux, M. Activation of autophagy in human skeletal muscle is dependent on exercise intensity and AMPK activation. FASEB J. 29, 3515‐3526 (2015). www.fasebj.org